Alien parasitic infections in the endangered Ryukyu long-furred rat (Diplothrix legata) on Amami-Oshima Island, Japan. (June 2020) - Tokiwa, Toshihiro; Yoshimura, Hisashi; Ito, Keiko; Chou, Shyun; Yamamoto, Masami
Abstract: There is limited knowledge about parasites of the endangered Ryukyu long-furred rat, Diplothrix legata (Murinae, Rodentia) endemic to Okinawa, Tokunoshima, and Amami-Oshima Islands in Japan. In the present study, postmortem histopathological examination of an individual found on Amami-Oshima Island revealed a mixed helminth infection of Calodium hepaticum, Hydatigera taeniaeformis, and Angiostrongylus cantonensis. These helminths are considered non-native to Amami-Oshima Island and are maintained by invasive mammals, such as non-native rats and outdoor cats. This observation presents a new host record for C. hepaticum and H. taeniaeformis and the first record of A. cantonensis in Ryukyu long-furred rat on Amami-Oshima Island. Graphical abstract: Unlabelled Image Highlights: Three parasites infected an endangered Diplothrix legata on Amami-Oshima Island This is a new host record for Calodium hepaticum and Hydatigera taeniaeformis This is the first record of A. cantonensis in D. legata on Amami-Oshima Island Invasive helminths reported on Amami-Oshima Island threaten endemic animals